Development of particle size and shape measuring system for machine-made sand. (17th November 2019) - Yang, Jian-Hong; Fang, Huai-Ying; Chen, Si-Jia
Abstract: In recent years, the use of machine-made sand has gradually increased. Simultaneous monitoring of the particle size and shape of machine-made sand during its production is vital. Here, a machine-made sand size measuring methods were developed using vibration dispersion and high-speed video imaging and subsequently evaluated. Moreover, a software system for particle size and shape identification of machine-made sand was also developed using image processing algorithms. Experiment studies on this system were conducted, and the results show that the measurement results of particle size between the vibration screening method and imaging method are different. The measurement results of particle size obtained from the imaging method were affected by the degree of dispersion and particle shape of the machine-made sand. The particle shape parameter of the machine-made sand was modified to compensate for the measurement results of particle size. After compensation for measurement results of the sand size by the imaging method, the cumulative curve of the particle size distribution was in agreement with that obtained from the vibratory sieve method; the measurement error of sand size is less than 3%. Based on sphericity characterization of the particles, the particle shape measurement using the imaging method was accurate. Thus, the particle size and shape measuring system based on imaging method met the monitoring requirements for machine-made sand.